2017
DOI: 10.1542/peds.2016-2037
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sleep, Food, and Activity in Infants for Obesity Prevention: An RCT

Abstract: The few existing early-life obesity prevention initiatives have concentrated on nutrition and physical activity, with little examination of sleep. METHODS:This community-based, randomized controlled trial allocated 802 pregnant women (≥16 years, <34 weeks' gestation) to: control, FAB (food, activity, and breastfeeding), sleep, or combination (both interventions) groups. All groups received standard well-child care. FAB participants received additional support (8 contacts) promoting breastfeeding, healthy eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 38 publications
2
86
0
1
Order By: Relevance
“…Data were available for 2196 of 2324 mother‐child dyads randomized across the four trials . Table illustrates the baseline sociodemographic variables of participants in the four individual trials and for the total combined dataset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were available for 2196 of 2324 mother‐child dyads randomized across the four trials . Table illustrates the baseline sociodemographic variables of participants in the four individual trials and for the total combined dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviations: AUS, Australia; BMI, Body Mass Index; EPOCH, Early Prevention of Obesity in CHildren Collaboration; HBT, Healthy Beginnings Trial; InFANT, Infant Feeding Activity and Nutrition Trial; N, number of participants with the event; Nourish, Nourish trial; NZ, New Zealand; POI, Prevention of Obesity in Infancy trial; SD, Standard Deviation; %, percentage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were excluded after comparison with other publications from the same cohorts as they studied similar associations, but with binary outcomes or single outcomes vs. panel data. 7,[21][22][23] We included 19 studies in the systematic review (Tables 1 and 2). Two studies were based on analyses from the same cohort; project Viva, 24,25 presenting different followup times.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…5 Curtailed infant sleep and bedtime routine have recently been under the attention of pediatricians and youth health care workers and healthy sleep is part of newly developed lifestyle interventions during infancy. 4,[6][7][8][9][10] Infant sleep problems can be problematic and include sleep latency and night awakenings, both leading to reduced sleep duration, quality, and efficiency (% of time spent in bed that the child really sleeps). Systematic reviews and meta-analysis so far have looked at the association and dose-response effects of sleep duration at age 0-4 years 11,12 and age 0-18 years [13][14][15] and concluded that there is an inverse association between sleep duration and weight gain.…”
mentioning
confidence: 99%